-8+5x=-12x-1

Simple and best practice solution for -8+5x=-12x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8+5x=-12x-1 equation:


Simplifying
-8 + 5x = -12x + -1

Reorder the terms:
-8 + 5x = -1 + -12x

Solving
-8 + 5x = -1 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-8 + 5x + 12x = -1 + -12x + 12x

Combine like terms: 5x + 12x = 17x
-8 + 17x = -1 + -12x + 12x

Combine like terms: -12x + 12x = 0
-8 + 17x = -1 + 0
-8 + 17x = -1

Add '8' to each side of the equation.
-8 + 8 + 17x = -1 + 8

Combine like terms: -8 + 8 = 0
0 + 17x = -1 + 8
17x = -1 + 8

Combine like terms: -1 + 8 = 7
17x = 7

Divide each side by '17'.
x = 0.4117647059

Simplifying
x = 0.4117647059

See similar equations:

| 111-5X=10X+21 | | 10x-29=51 | | 5X+12=93+4X | | 8+11X=98+X | | 5x+13y=126 | | 2(3+3x)=6x+6 | | 2x+3x+6=10x-16 | | 3x+5y=70 | | 6x+31=14x-65 | | 4(x-8)=25.6 | | 6(a+1)=58.2 | | 6(a+1)= | | 8A+8B=-16 | | h=-16t^2+56+1 | | h=-16t^2+70t+10 | | -0.5=3c-5 | | 4x-10=4-x | | 7t-4=10t+14 | | 4x+12=7x+3 | | 7y-3y+y=25 | | -2a-9=6a+15 | | 9k+6=8k+13 | | 2x+40=11x-59 | | 8z+6=7z+4 | | 8+4q=16 | | 2w+1=5 | | 3x+40=6x+10 | | 8x+18=42 | | 11x-17=49 | | 5b-2=b+10 | | 4x+12x=6*6+4(11) | | t(t-6)(t+8)=0 |

Equations solver categories